Religio, pietas y sacrilegio en la iconografía monetaria de la Roma tardorrepublicana y altoimperial - Labrador Ballestero, Patricia; Vico Belmonte, Ana (Eikón / Imago, 2024)
Roman coinage presents a great variety of iconographic messages that show the close relationship between traditional religion, the transmission of messages by the state and coinage. This article analyses some of these messages and the link between coinage and sacrilege. To this end, we have selected key pieces of Late Republican and High Imperial Roman coinage, covering a chronological framework between approximately 133 BC and 192 AD, and we have studied the relationship between the types shown and their socio-political context.